Effect of Wollastonite on the ablation resistance of EPDM based elastomeric heat shielding materials for solid rocket motors. (August 2016) - Natali, Maurizio; Rallini, Marco; Kenny, Josè; Torre, Luigi
Abstract: EPDM/aramid fibers ablatives represent the state of the art Elastomeric Heat Shielding Materials (EHSMs) for Solid Rocket Motors (SRMs). Due to their mechanical properties and excellent thermal stability, aramid fibers or pulp constitute the common reinforcement of EPDM based formulations. Aramid fiber was introduced by NASA and space companies such as Orbital-ATK with the aim to replace asbestos. Space Shuttle's reusable SRMs and many ICBMs employed Nitrile butadiene rubber (NBR) loaded with asbestos (ASNBR) as a primary internal case insulation; however, due to cancerogenicity of asbestos, NASA sought a replacement for many years, but this goal has been very challenging to achieve since the comprehensive performance of ASNBR was and is still difficult to match. Wollastonite can be considered the only non-hazardous mineral/inorganic filler able to partially replace asbestos. Wollastonite is a calcium inosilicate mineral (CaSiO3 ) and the shape of the filler is acicular. Our study wanted to evaluate Wollastonite as a possible replacement of aramid pulp in the production of EPDM based EHSMs for solid rocket motors. The heat capacity, thermal and dimensional stability, mechanical properties, and ablation resistance of the produced materials were studied and here reported.